INFLUENCE OF THE STYLE OF PEDAGOGICAL COMMUNICATION ON THE MOTIVATION AND LEARNING ACTIVITY OF ADOLESCENT CHILDREN (American Journal of Pedagogical and Educational Research, 2022)
INFLUENCE OF THE STYLE OF PEDAGOGICAL COMMUNICATION ON THE MOTIVATION AND LEARNING ACTIVITY OF ADOLESCENT CHILDREN